High strength potential of aluminium nanocomposites reinforced with nonperiodical phases. (24th March 2005) - Nagy, J.; Balog, M.; Izdinsky, K.; Simancik, F.; Svec, P.; Janickovic, D.
Extrusion of rapidly solidified Al94 V4 Fe2 ribbons and Al94 V4 Fe2 /Al powder mixtures was studied. TEM studies revealed microstructural heterogeneity in as-received ribbons containing α-Al, quasicrystalline, nanoscale amorphous and Al10 V intermetallic phases. Bulk profiles containing different amounts of cryo-milled Al94 V4 Fe2 particles and Al powders were prepared via hot extrusion. Temperature was found to play the decisive role in the extrusion process. The lack of plasticity led to insufficient material flow during extrusion and was found responsible for the formation of macroscopic voids. Al94 V4 Fe2 extruded bars exhibited quite satisfactory properties in compression tests, however preliminary failed in tensile tests due to insufficient consolidation. The addition of 1 mm Al powder into the Al94 V4 Fe2 particles yielded extrusions at lower loads or at lower temperatures, resulting in composite samples with Al matrix reinforced with nanoscale nonperiodic phases. This approach appeared quite promising for the overall design of applicable technological routes inducing the non-periodic structures into bulk profiles.